The Influence of Islamic Social Reporting and Sustainability Performance on the Financial Performance of Sharia Banks - Arista Putri Andriani; Nur Fatoni; Mardhiyaturrositaningsih Mardhiyaturrositaningsih (INSTITUT AGAMA ISLAM SEBI, 2026)
This study aims to examine the extent to which Islamic Social Reporting (ISR) and Sustainability Performance (SP) influence the financial performance of sharia-based banks. The methodology is quantitative, employing a causal-associative approach. The panel data consist of 13 Sharia Commercial Banks observed over the 2021–2024 period, resulting in a total of 52 observations. The analysis was carried out using panel data regression with Common Effect Model specifications using the EViews application. The ISR variable was quantified using a 48-item disclosure index, while SP was measured through Weighted Content Analysis on 58 Global Reporting Initiative (GRI) indicators relevant to the banking sector. The results of the analysis show that ISR and SP have a significant positive influence on the financial performance of Islamic banks. These findings imply that improving the quality of Islamic value-based social responsibility disclosure and sustainability reporting contributes significantly to the profitability growth of Islamic financial institutions.